ESTAÇÃO AGROMETEOROLÓGICA PARA PEQUENOS AGRICULTORES AUTO - SILVA, EDUARDO; KOTLINSKI, ELISEU; LEANDRO, GIDEON; TURCHIELLO, GILSON D. M.; REIMBOLD, MANUEL M. P.; DAMIÃO, MATEUS; ECKHARDT, MOACIR; VIEIRA, PAULA K. P. (Salão do Conhecimento, 2013)
Resumo